Legal Analysis of Online Loan Interest Rates from the Perspective of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Competition - Trinah Asi Islami; Meirza Aulia Chairani (Universitas Darunnajah Jakarta, Indonesia, 2026)
This study analyzes the regulation of online loan interest rates from the perspective of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, with a focus on KPPU Decision No. 05/KPPU-I/2025, which found that 97 fintech lending operators violated Article 5(1)(a) through collective price-fixing practices via the Indonesian Joint Funding Fintech Association (AFPI). Using a normative legal research method with a statutory approach and a conceptual approach, this study evaluates the alignment between OJK sector regulations (POJK No. 77/2016 as amended by POJK No. 40/2024) and KPPU competition law. Key findings indicate that the AFPI’s interest rate arrangement (from 1% to 0.3% per day) satisfies both subjective (horizontal agreements through meetings and digital communication) and objective (market distortion: 95% price uniformity, 27% reduction in innovation, 62% entry barriers) elements. A structural legal conflict arises between the OJK’s consumer protection mandate and the KPPU’s market competition mandate, creating regulatory arbitrage where sector compliance constitutes a horizontal violation. A comparative analysis confirms that vertical regulatory models (India-RBI, UK-FCA) are more effective than AFPI’s self-regulation. Critical discussions highlight the regulatory paradox: the intent to protect consumers actually hinders market efficiency and credit access for the unbanked segment. The study recommends systemic reforms, including vertical regulation by the OJK, an OJK-KPPU joint task force, repositioning the AFPI’s functions as soft law, and harmonizing Law No. 4/2023 on the Development and Strengthening of the Financial Sector (P2SK Law) with Law No. 5/1999 (Anti-Monopoly Law). This case sets a precedent that the state regulator has exclusive authority over price setting in the platform economy, while also serving as a momentum for the transition from self-regulation to convergent oversight for a sustainable fintech ecosystem.